2016
DOI: 10.1172/jci88619
|View full text |Cite
|
Sign up to set email alerts
|

γ-Secretase inhibitor–resistant glioblastoma stem cells require RBPJ to propagate

Abstract: C o m m e n t a r y 2 4 1 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
4
0
2
Order By: Relevance
“…In another approach, γ secretase inhibitors were found resistant for brain tumor initiating cells with high level of RBPJ. Targeting CDK9 or c-MYC, an upstream regulator of RBPJ, with small molecules also decreased BTIC propagation, and prolonged survival in mice bearing orthotopic GBM xenografts [41].…”
Section: Cdk6 Inhibitorsmentioning
confidence: 96%
“…In another approach, γ secretase inhibitors were found resistant for brain tumor initiating cells with high level of RBPJ. Targeting CDK9 or c-MYC, an upstream regulator of RBPJ, with small molecules also decreased BTIC propagation, and prolonged survival in mice bearing orthotopic GBM xenografts [41].…”
Section: Cdk6 Inhibitorsmentioning
confidence: 96%
“…Активация сигнального пути Notch служит также триггером для прогрессии опухоли в более агрессивный фенотип. Исследования in vitro и in vivo показали, что блокирование сигнального пути Notch ингибиторами γ-секретазы приводило к снижению роста опухоли, индукции апоптоза, даун-регуляции ММП-2 и 9 и, как результат, снижало метастазирование [41,42]. При блокаде сигнального пути Notch с помощью ингибиторов γ-секретазы в опухолевых клетках рака мозга было обнаружено снижение доли CD133-положительных клеток (СКО) в 5 раз.…”
Section: обзоры литературыunclassified
“…При блокаде сигнального пути Notch с помощью ингибиторов γ-секретазы в опухолевых клетках рака мозга было обнаружено снижение доли CD133-положительных клеток (СКО) в 5 раз. Уровень апоптоза был также выше -почти в 10 раз [42]. Продолжаются клинические испытания с антителами к DLL-4 и Notch-1 [43].…”
Section: обзоры литературыunclassified
“…Basic and clinical trials have reported the antitumor activity of GSIs, although these studies have been conducted on a small sample size of solid tumors [ 29 ]. Apart from inhibiting cell proliferation and inducing cell apoptosis by inhibiting the crack of Notch-3, GSI is associated with increasing the sensitivity of NSCLC cell lines to platinum chemotherapy, supporting the concept that GSI can be useful in chemotherapy treatment and recurrent cancer [ 30 ]. Thus, it is necessary to explore the molecular mechanisms in order to obtain greater insight into the role of GSI in the treatment of NSCLC.…”
Section: Introductionmentioning
confidence: 96%